2019
DOI: 10.1155/2019/1094520
|View full text |Cite
|
Sign up to set email alerts
|

Marinobufagenin Inhibits Neutrophil Migration and Proinflammatory Cytokines

Abstract: Cardiotonic steroids, such as ouabain and digoxin, are known to bind to Na+/K+-ATPase and to promote several biological activities, including anti-inflammatory activity. However, there are still no reports in the literature about inflammation and marinobufagenin, a cardiotonic steroid from the bufadienolide family endogenously found in mammals. Therefore, the aim of this work was to analyze, in vivo and in vitro, the role of marinobufagenin in acute inflammation. Swiss mice were treated with 0.56 mg/kg of mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…In vitro studies also presented the inhibitory effect of ouabain on rabbit (Ward and Becker, 1970), human (Ray and Samanta, 1997), and mice neutrophil chemotaxis (Cavalcante-Silva et al, 2021a). The cardiotonic steroid marinobufagenin also reduces neutrophil migration during inflammation, corroborating the ouabain effect (Carvalho et al, 2019) (Figure 1B).…”
Section: Neutrophils: Modulation By Ouabainsupporting
confidence: 57%
“…In vitro studies also presented the inhibitory effect of ouabain on rabbit (Ward and Becker, 1970), human (Ray and Samanta, 1997), and mice neutrophil chemotaxis (Cavalcante-Silva et al, 2021a). The cardiotonic steroid marinobufagenin also reduces neutrophil migration during inflammation, corroborating the ouabain effect (Carvalho et al, 2019) (Figure 1B).…”
Section: Neutrophils: Modulation By Ouabainsupporting
confidence: 57%
“…An interesting feature is that Na + /K + -ATPase isoforms are expressed in a cell-/tissue-specific fashion ( Blanco, 2005 ), ( Cereijido et al, 2012 ), ( Geering, 2008 ): the α1 isoform is ubiquitously expressed in mammalian tissues and, in rodents, it is 100–1000-fold less sensitive to cardiotonic steroids. In contrast, it has been shown not to be the case for the bufadienolide marinobufagenin ( Fedorova and Bagrov, 1997 ), ( Fedorova et al, 2001 ), although our group reported that it behaves similar to any known cardiotonic steroid ( Godinho et al, 2017 ), ( Carvalho et al, 2019 ); the α 2 isoform is found in striated and smooth muscle, as well as in both astrocytes and neurons in the central nervous system, and adipose tissue; the α 3 isoform is basically found in neurons but not in astrocytes and should be considered a neuronal marker ( Dobretsov and Stimers, 2005 ); the α 4 isoform is specifically found in the midpiece of sperm ( Blanco, 2005 ). The β subunit is a type II glycoprotein of around 300 amino acids, that is, fundamental for a normal pumping activity.…”
Section: Introductionmentioning
confidence: 82%
“…It was demonstrated [91] that administration of ouabain in a dose of 0.56 mg/kg to mice infected with Leishmania (L.) amazonensis resulted in a decrease of peritoneal migration of macrophages and in the production of two proinflammatory cytokines interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α) and had no cytotoxic effects on macrophages. Intraperitoneal injection of marinobufagenin in a dose of 0.56 mg/kg to mice showed a decrease in zymosan-activated production of proinflammatory cytokines IL-1β and IL-6, without affecting the level of TNF-α [92]. The treatment of peritoneal macrophages with different concentration (10, 100, 1000, and 10000 nM) of marinobufagenin in vitro showed no cytotoxic effect.…”
Section: Mononuclear Cells/macrophagesmentioning
confidence: 92%